Perlindungan Hak Anak Dalam Perkawinan Poligami Di Indonesia - Nurul Aini (De Jure: Jurnal Hukum dan Syari'ah, 2017)
The problem of polygamy is actually not only related to the relationship between husband and wife, but also concerns how children can still develop their potential. Some children's problems do not entirely become the responsibility of the family, but also the government. The purpose of this study is to describe the protection of children in polygamous marriage according to Muhammad Syahrur viewed from the perspective of Law No. 23 of 2002 concerning Child Protection. This research belongs to normative juridical research using statute approach and conceptual approach. The results showed based on the hudûd theory of Muhammad Syahrur that Shahrur's thoughts on polygamy were in line with what the Indonesian government was trying to maintain and protect children's rights even though in the different forms. In addition, according to the researcher, it needs to be added regarding the cumulative requirements contained in Law No. 1 Number 1974 concerning Marriage as contained in Article 2 letter b and d of Law No. 23 of 2002 concerning Child Protection as a condition for a husband to apply for polygamy.Problematika poligami sebenarnya bukan terkait hubungan antara suami dan istri saja, tetapi juga menyangkut bagaimana anak tetap bisa mengembangkan potensinya. Sebagian persoalan anak memang tidak sepenuhnya menjadi tanggung jawab keluarga, tetapi juga pemerintah. Tujuan penelitian ini adalah untuk mendeskripsikan perlindungan anak dalam perkawinan poligami menurut Muhammad Syahrur ditinjau dari perspektif UU No. 23 Tahun 2002 tentang Perlindungan Anak. Penelitian ini tergolong penelitian yuridis normatif dengan menggunakan statute approach dan conceptual approach. Hasil penelitian menunjukkan berdasarkan teori hudûd Muhammad Syahrur bahwa pemikiran Syahrur tentang poligami tersebut sejalan dengan apa yang diupayakan pemerintah Indonesia untuk memelihara dan melindungi hak-hak anak meskipun dari bentuk dan perwujudannya berbeda. Selain itu, menurut peneliti perlu ditambahkan terkait persyaratan kumulatif yang terdapat dalam UU No. 1 Tahun 1974 tentang Perkawinan sebagaimana yang terdapat dalam Pasal 2 huruf b dan d UU No. 23 Tahun 2002 tentang Perlindungan Anak sebagai syarat seorang suami akan mengajukan permohonan poligami.